Agama dan Keamanan - Semy Arayunedya (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
The change in the security paradigm still remains an opportunity for religions to make the bargaining power of ideas  about world’s affairs. People and  religion institutions should participate and contribute on  exact science to the humanities  from the present range to the future. Certainly, it doesn't just stop when we  work hard to help natural disasters victims,  overcoming poverty, uphold human rights, or fight for a decent living environment, and the universal mission of religion  but also to focus on human flourishing. This mission can only be accomplished by turning from the love of pleasure, which is the main axis of today's culture, to the pleasure of love.